2018
DOI: 10.1021/acsanm.8b00201
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting of Swollen Poly(3-hexylthiophene) Films during Spin-Coating Processes: Implications for Device Fabrication

Abstract: Poly­(3-hexylthiophene) (P3HT) films have been usually prepared by spin-coating for the applications of electronic devices such as organic photovoltaic devices (OPV) and organic field-effect transistors (OFETs). The wetting and dewetting behaviors of the swollen P3HT films during the spin-coating processes, however, are still poorly understood. In this work, we investigate the dewetting behaviors of P3HT thin films and the formation of ring structures during the spin-coating process by controlling the spin rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This observation is consistent with a recent report by Chung et al . on the formation of ring structures in polymer thin films . During the spin‐coating process, the polymer chains delocalize with growing dewetted rings for volume conservation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with a recent report by Chung et al . on the formation of ring structures in polymer thin films . During the spin‐coating process, the polymer chains delocalize with growing dewetted rings for volume conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Interesting nanostructures such as pancake‐like aggregates, zigzag structures and Janus and tripod structures were observed depending on the polymer chain conformations . Most of these observations were attributed to the effects of substrate, solvent, solution concentration, solution temperature, spin coating rate, film thickness and polymer molecular weight . During the past few decades, the wettability of polymers on surfaces has evolved as an important topic of research because it critically controls technological applications ranging from fluorescent coatings to sensors, photovoltaic cells and other thin‐film‐based organic electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, emerging research now focused on introducing controlled holes into polymer nanofilms or coatings in order to tune better molecular aggregations by rims of holes and thus better emitting and charge transport properties. , The classical approach in introducing controlled holes was based on first preparing nanofilms of the polymer mixture, such as poly­(3-hexylthiophene) (P3HT) with polystyrene (PS), polyethylene glycol, and so forth, and then dissolving one component after fully phase separation. , Recently, a more direct approach was proposed, by which the hole morphology was simply controlled through dewetting during preparation. Chen et al studied the dewetting morphology of P3HT thin films after spin-coating. Quantitative analysis revealed that size of ring-shape holes was affected by both dewetting time and formation of P3HT nanowhiskers.…”
Section: Introductionmentioning
confidence: 99%
“…Nascent holes, that is, ring structures or pinholes, appear after the spin-coating process, particularly severe when the substrate was poor wetting. Therefore, variation in even a single factor, such as preparation atmosphere, solvent, spin speed, immersion time (the amount of time the solution stays on the substrate), and so forth, may finally result in a dramatic change in the structure of the film. ,,, Our previous work demonstrated the morphological changes in nascent holes induced by film thickness, in atmosphere during spin-coating, and in interfacial properties. Moreover, the study on the nascent holes provided us a unique tool to reveal formation of nanofilms at various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the rims of adjacent growing holes coalesce, leading to the formation of cellular Voronoi tessellation patterns, followed by their subsequent disintegration into isolated, random droplets due to Rayleigh instability. Most initial experiments on dewetting were performed with thin homopolymer films, such as polystyrene (PS), poly­(methyl methacrylate) (PMMA), etc., either heated above the glass-transition temperature ( T G ) or exposed to solvent vapor. However, dewetting-mediated self-organization has also been observed in thin films of various other materials, such as polymer blends, block copolymers, conjugated polymers, , sol–gel-derived inorganic materials, liquid crystals (LCs), and so on. While spontaneous disintegration of thin films is undesirable from the standpoint of coatings, the same phenomenon has emerged as a potential tool for nonlithographic mesopatterning, water harvesting, enhancement of photoluminescence in optoelectronic devices, and so on.…”
Section: Introductionmentioning
confidence: 99%